The External Factors of Students’ Involvement in Speaking Activity at SMP Progresif Bumi Shalawat - M.A. Nurul Haikal (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2016)
This research is conducted to know what factors that influence the students’ involvement in speaking activity in order to practice their speaking skill and what strategies that the teacher used to encourage those external factors. This research uses descriptive qualitative method. There are two instruments used for this research, namely, class observation and interview. Based on the results of class observation and interview, the researcher concludes that teacher factor gives the greatest impact on students’ involvement and the appropriate strategies can support those external factors.